Diseño e implementación de un Sistema de localización personal para Área Cerrada. - Carrasco Cobos, Jenny Elizabeth (2016)
The research paper details the design and implementation of a personal location system for enclosing area, consists of three parts: transmission, reception and control. The transmission blocks sends an area code, to the receiver comparing the code to determine the location area , it sends a data to the control block, which consists of an interface data collection, developed in Visual BASIC, the data obtained are displayed in real time and stored in a database. For establishing communications between the blocks, microcontroller 16F628A, radio frequency modules 434 and Transceivers HR-1020 were used, allowing communication between blocks also shows the design of plates and at all stages of development . Finally made different performance tests, taking location data to verify the operation of the proposed total area, dividing the system in suitable areas.